Adrenal cortex–medulla interactions in adaptation to stress and disease. (October 2019) - Bornstein, Stefan R.; Berger, Ilona; Scriba, Laura; Santambrogio, Alice; Steenblock, Charlotte
Abstract: The adrenal gland plays a major role in response to physiological challenges and is able to adapt to homeostatic alterations. The adrenal is composed of two different tissue types in a bidirectional connection, the medulla, and the cortex. Already during adrenal organogenesis, close interactions between the two parts are necessary for the differentiation and morphogenesis of the gland. Moreover, communication between the cortex and the medulla ensures a regular function of the adult adrenal. Proper adaptation is of particular importance because dysregulation of the stress system is the cause of various diseases. In the current review, we summarize the significant progress made in the understanding of the cortical–chromaffin communications in stress and disease during the last couple of years.